Computation of viscous compressible turbulent aerodynamic flows - Lee, Alex Khueh Hock. (2009)
A general proof-of-concept prototype multiblock system, which provides Euler and Navier-Stokes flow solution capability for complex configurations, has been developed. The flow system is formulated on a multiblock concept which divides the flow field into non-overlapping blocks, arranged so that body-conforming grids are defined by the node-to-node interface of the grids at the block face, thus allowing complex geometrical shapes to be modeled more easily and with greater numerical accuracy than with a single block. The multiblock algorithm not only greatly facilitates the solution of complex problems, but also offers in-core computation since only one block needs to reside in the core memory of a computer at any given time while the remaining blocks residing on an external device. The multiblock scheme also increases the maximum total allowable size of the computational problem, and permits multiple block grids with millions of grid points to be generated and used on computers with enough internal memory for a small percentage of the total grid data.